Karakteristik pasien psoriasis di SMF Ilmu Kesehatan Kulit dan Kelamin Rumah Sakit Uumum Pusat H. Adam Malik Medan periode Januari 2010-Desember 2012 - Wahyuni Widiyanti Suhoyo; Chairiyah Tanjung; Kristo A Nababan (Fakultas Kedokteran USU, 2013)
Introduction : Psoriasis is a common, chronic, and recurrent erythropapulosquamous disease of the skin, characterized by erythematous plaques covered by silvery white scales.Determine the characteristics of psoriasis patients in dermatovenereology department Haji Adam Malik Hospital Medan periode January 2010 to December 2012.Method : A retrospective study was performed based on the medical records of psoriasis patients from January 2010 to December 2012.Results : There were 75 cases of psoriasis; 47 male (62.7%) and 28 female (37.3%). Most of the cases (29 cases) was found at the age of 46-60 years old group (38.8%). The majority of the ethnic is Batak (47 cases; 62.7%). The majority of patient education is high school graduate (34 cases; 45.3%). Psoriasis mostl suffered by civil servant and and self-employed individual each of them are 19 cases (25.3%). The commonest clinical type was psoriasis vulgaris 61 cases (81.3%).Conclusion : In Haji Adam Malik Medan general hospital, psoriasis prevalency is higher in male, age group 46-60 years, the ethnics are Batak, high school graduate, civil servant and self-employed. Most type of psoriasis is psoriasis vulgaris. Keywords : psoriasis; characteristic